2022
DOI: 10.1111/asap.12332
|View full text |Cite
|
Sign up to set email alerts
|

Realigning individual behavior with societal values: The role of planning in injunctive‐norm interventions aimed at increasing voter turnout

Abstract: Voting is highly valued in democratic societies. However, in recent years there has been a marked decline in voting. To realign voting behavior with democratic values, we turn to the study of injunctive‐norm interventions. These interventions advance that by making injunctive norms, the norms representing collective values, salient to a targeted group of individuals, individuals will likely conform to the promoted norm. However, studies testing the effectiveness of injunctive‐norm interventions have produced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Anderson et al (2018) found that, in addition to making a voting plan, individuals need to be exposed to relevant, clear information material about the election. Furthermore, the salience of norms that represent a group's collective values influences voting intentions, regardless of how close or significant a group (e.g., friends, family) is to the individual (Bourgeois & de la Sablonnière, 2023).…”
Section: Voter Disenchantmentmentioning
confidence: 99%
“…Anderson et al (2018) found that, in addition to making a voting plan, individuals need to be exposed to relevant, clear information material about the election. Furthermore, the salience of norms that represent a group's collective values influences voting intentions, regardless of how close or significant a group (e.g., friends, family) is to the individual (Bourgeois & de la Sablonnière, 2023).…”
Section: Voter Disenchantmentmentioning
confidence: 99%